CDM Potential in Palm Solid Waste Cogeneration as an Alternative Energy in Aceh Province - Mahidin, Mahidin; Machdar, Izarul; Faisal, Muhammad; Nizar, Muhammad (UI Scholars Hub, 2012)
Empty Fruit Bunch (EFB) as a solid waste in Crude Palm Oil (CPO) industry does not utilized yet as an alternative energy source to generate electricity. It is well known that use of solid wate (biomass) as an energy source is part of the Clean Development Mechanism (CDM) scheme due to direct reduction of Green House Gases (GHGs) emission and provide a direct contribution to sustainable development. Utilization of EFB as a source of energy is very potential to be implemented in Aceh since this province has 25 CPO Mills at the moment which actively produce about 870,000 ton EFB per year. This study is subjected to evaluate the potency of electricity from EFB theoretically by using primary data (survey data) and secondary data. Potency of EFB and number of electricity produced from that EFB are estimated using primary data and direct combustion scenario, respectively. Calculation methods for emission reduction acieved are done by AMS-I.D: Renewable electricity generation to the grid and AMS-III.E: Methane emissions avoided from dumping at a solid waste disposal site. The result of this investigation shows that energy consumption in 25 CPO Mills is 45 GW(e)h per year. Evidently, the number of energy/electricity which is potential to be produced by using 75% EFB is 1,047 GWh per year; so that the GHGs emission reduction up to 171,232.21 tCO2e per year.